Respuesta :

Answer:

Step-by-step explanation:

If y= x + 4 then plug it into the other equation where the y is. So 5x + x +4=22. Then solve.

for x                                                                              for y

5x + x + 4=22                                                               y=x +4

6x+4=22                                                                         y=3+4

22-4=18                                                                            y=7

6x = 18

18/6=3                                                      

x=3                                                         so, x=3 and y=7